THE ENCOUNTER OF PROPHET MOSES WITH THE INTERNAL SCIENCE OR KHIDR PARABLE - Arslantaş, Yüksel; Şahin, Resul (Hamza ALTIN, 2022)
The story of Prophet Moses and Khidr in the Qur'an is not mentioned in the Torah. For this reason, it has been claimed by Western researchers that this story in the Qur'an was influenced by the legends of some cultural basins and comparisons were made. But there is no similarity between the legends they put forward and the story in the Qur'an. Because in the mythology they claim, the belief of polytheism is dominant, and in the story of the Qur'an, the belief of tevhid is dominant. In the Qur'an, Hz. It is clearly stated that Moses is a prophet, Hz. Signs of Khidr's prophecy are given. Even if we accept the view that he is not a prophet, it is clearly stated that he is a righteous person. Muslim scholars, on the other hand, they disagreed on the identity of Khidr, whether he was a prophet or a saint, and whether he was immortal. In our article, we will try to explain the reasons why it is not included in the Torah and the issues on which Islamic scholars disagree.

Kur’an’da yer alan Musa Peygamber ve Hızır kıssası Tevrat’ta geçmemektedir. Bu nedenle Batılı araştırmacılar tarafından, Kur’an’daki bu kıssanın, bazı ku?ltu?r havzalarına ait efsanelerden etkilenmiş olduğu iddia edilmiş ve karşılaştırmalar yapılmıştır. Fakat ileri su?rdu?kleri efsaneler ile Kur’an’da geçen kıssanın benzerliği yoktur. Zira iddia ettikleri mitolojide politeizm inancı, Kur’an’daki kıssada ise tevhit inancı hâkim durumdadır. Kur’an’da Hz. Musa’nın peygamber olduğu açıkça belirtilmiş, Hz. Hızır’ın peygamberliğine dair işaretler verilmiştir. Peygamber olmadığı göru?şu?nu? kabul etsek dahi salih bir kişi olduğu açık olarak beyan edilmiştir. Mu?slu?man âlimler ise, Hz. Hızır’ın kimliği, peygamber mi, yoksa veli mi olduğu, ölu?msu?z olup olmadığı konularında ihtilaf etmişlerdir. Makalemizde, gerek Tevrat’ta yer almamasının sebeplerini ve gerekse İslam âlimlerinin ihtilaf ettiği konuları açıklamaya çalışacağız.
HZ. MUSA’NIN BÂTINİ İLİMLE KARŞILAŞMASI VEYA HIZIR KISSASI